020 Comprehensive cardiovascular magnetic resonance assessment of anderson-fabry cardiomyopathy- natural history and assessment of treatment effect. (3rd April 2017) - Reid, Anna; Miller, Chris; Jovanovic, Ana; Woolfson, Peter; Abidin, Nik; Clark, David; Gamlin, Wendy; Coutts, Glyn; Schmitt, Matthias
Abstract : Background: The Anderson Fabry Cardiomyopathy (AFC) is heterogeneous, complex, and its pathophysiology remains incompletely understood. There is uncertainty regarding the optimal timing and impact of enzyme replacement therapy (ERT) in cardiac involvement, with a pressing need for biomarkers able to identify early disease, monitor and guide treatment. Objectives: The aims of this study were two-fold: 1) to perform comprehensive cardiac phenotyping in a large cohort of Anderson-Fabry disease (AFD), and 2) characterise their short-term natural history and assess the impact of ERT using multi-parametric Cardiac Magnetic resonance imaging (MPCMRi), echocardiography and ECG analysis. Methods: 113 prospectively enrolled, genetically-confirmed, AFD patients were compared to 20 age-matched healthy volunteers (HVs). 37 of these patients re-attended for a one-year follow-up scan, and were sub-grouped according to treatment status (newly started on ERT, ERT naïve, and established on ERT). Results: The AFC is characterised by increased LV mass of several different hypertrophic patterns, impaired LV global longitudinal strain and left atrial function, low myocardial native T1, high T2, and increased extracellular volume fraction. Significantly higher T1s were seen in the inferolateral wall, even before the development of increased wall thickness or LV mass, or LGE. A newly proposed marker of disease severity, the 'T1 ratio', reflects the relationship between inferolateral and remote myocardial T1, and strongly correlated with LV mass, percentage LGE and ECV fraction, whilst avoiding potential uncertainty caused by pseudo-normalisation of T1s in severe AFD. ERT initiation reduced LVM. T1 values (excluding the inferolateral wall) fell significantly in untreated patients (974±36 ms v 955±44 ms, p=0.04) associated with a significant increase in voxel based spread (288 v 350, p=0.02), whereas both treatment groups showed no change in T1 values. The T1 ratio showed a trend towards improvement (0.94±0.08 v 0.98±0.1, p=0.05) in the established ERT group. Electrocardiography and echocardiography did not detect disease progression or treatment effects in any group. Conclusions: AFC is a complex pathology with intracellular and extracelluar disease components. MPCMRi elucidates these disease processes and allows early disease detection, and possibly disease and treatment monitoring.